High efficiency dye-sensitized solar cells with a novel two dimensional Cd-V-LDH photoanode - Bendary, Samar H.; Hashem, Amira A.; Mahmoud, Sawsan A. (Frontiers in Materials, 2023)
The present study demonstrates a novel photoanode layer double hydroxide (LDH) for dye-sensitized solar cells (DSSCs). The search for a photoanode (PA) with low cost and high power conversion efficiency (PCE) has become one of the most significant challenges facing researchers. LDH has proven successful as a photocatalyst in various fields. In this paper, a novel Cd-V-LDH with a molar ratio of Cd:V = 1:1 was synthesized by the coprecipitation method and used as a novel PA in DSSCS. The prepared Cd-V-LDH was investigated by X-ray diffraction (XRD), Raman spectroscopy, Scanning electron microscope (SEM), Fourier Transform infrared spectroscopy (FTIR), Nitrogen sorption analysis , UV–Vis absorption spectrum, Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). Eosin Y (EY) as a photosensitizer, LiI-I2 as a liquid electrolyte, and g-C3N4 (GN) as a counter electrode (CE). The Series cells of DSSCs were assembled and the available variables have been studied to achieve the best performance under normal conditions. these variables, e.g., concentration and pH of EY, active area of PA, and different types of PC, e.g., graphene oxide (GO), commercial carbon (CC), and (GN). The photovoltaic parameters were observed to be 705 mV and 12.40 mA/cm2 for open circuit voltage (VOC) and short circuit current density (JSC), respectively, for the CdV-LDH/EY/LiI-I2/GN system. The assembled cell with Cd-V-LDH/EY/LiI-I2/GN having a PCE of 5.4% is comparable to Cd-V-LDH/EY/LiI-I2/GO and Cd-V-LDH/EY/LiI-I2/CC, which have 4.9% and 3.8%, respectively, at the same testing conditions.